(untitled) (Journal of Philosophy Culture and Political Science, 2015)
This article examines the religious text and its juridical hermeneutics in the works associated with the foundation of Islamic jurisprudence: "AlUafi" and "Al-Kafi", well known theologist and legal scholar of the Kazakh steppes in XIII century Husamuddin al-Sygnak.